Female philopatry may influence antipredatory behavior in a solitary mammal - Alexandra Burnett; Michelle Hein; Natalie Payne; Karla L. Vargas; Melanie Culver; John L. Koprowski (PeerJ)
Whether neighboring individuals are related or not has a number of important ecological & evolutionary ramifications. Kin selection resulting from philopatry can play an important role in social and antipredatory behavior. Ground squirrels exhibit alarm vocalizations in the presence of predators; however, the degree to which kin selection shapes alarm calling behavior varies with species ecology and the degree of relatedness between neighbors. We studied a solitary ground squirrel species that exhibits sex-biased calling propensity to determine if female philopatry may be responsible for sex differences in antipredatory behavior observed in our population. We used double digest restriction-site associated DNA sequencing (ddRADseq) to sample the genomes of Harris’s antelope squirrel (Ammospermophilus harrisii) to determine the relatedness between individuals and test whether genetic and geographic distance were correlated. We found that geographic distance had a positive relationship with genetic distance, and that this relationship was sex-dependent, suggesting male-biased dispersal. Our results provide supporting evidence that female philopatry may be responsible for higher calling propensity observed in female squirrels, potentially influencing antipredatory behavior in this species via kin selection. Our findings add to a growing body of evidence that philopatry is an important ecological driver influencing sociospatial organization in solitary species.